Integrated Immunopeptidomic and Proteomic Analysis of COVID-19 lung biopsies - Yin, Shanye; Klaeger, Susan; Chea, Vipheaviny A.; Carulli, Isabel P.; Rachimi, Suzanna; Black, Katharine E.; Filbin, Michael; Hariri, Lida P.; Knipe, Rachel S.; Padera, Robert F.; Stevens, Jonathan D.; Lane, William J.; et al. (Frontiers in Immunology, 2023)
Severe respiratory illness is the most prominent manifestation of patients infected with SARS-CoV-2, and yet the molecular mechanisms underlying severe lung disease in COVID-19 affected patients still require elucidation. Human leukocyte antigen class I (HLA-I) expression is crucial for antigen presentation and the host's response to SARS-CoV-2. To gain insights into the immune response and molecular pathways involved in severe lung disease, we performed immunopeptidomic and proteomic analyses of lung tissues recovered at four COVID-19 autopsy and six non-COVID-19 transplants. We found signals of tissue injury and regeneration in lung fibroblast and alveolar type I/II cells, resulting in the production of highly immunogenic self-antigens within the lungs of COVID-19 patients. We also identified immune activation of the M2c macrophage as the primary source of HLA-I presentation and immunogenicity in this context. Additionally, we identified 28 lung signatures that can serve as early plasma markers for predicting infection and severe COVID-19 disease. These protein signatures were predominantly expressed in macrophages and epithelial cells and were associated with complement and coagulation cascades. Our findings emphasize the significant role of macrophage-mediated immunity in the development of severe lung disease in COVID-19 patients.